(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
By utilising laboratory model footing tests, the performance of foundations on clay soil reinforced with geotextile was examined. The steel plate used to make the square model footing had dimensions of 250 mm by 250 mm. The length of the reinforcement layers, the type of geotextile, and the top layer spacing were among the parameters examined in this study. According to the test findings, adding reinforcement could greatly increase the soil’s bearing capacity and lessen footing settlement. The increase in BCR values varied depending on the type of geotextile, its position and how it dealt with the soil. BCR increases as u/B increases until it reaches a certain point where it decreases. The maximum improvement is achieved at u/B=0.67 for both types, this improvement varying depending on the length of the geotextile. The values of L/B that achieve a higher BCR is 8 for woven and nonwoven. The save length ratio that produce positive effect in all position is L/B=6.67. how-ever, in practice, nonwoven can achieve excellent performance with less reinforcement than woven.